Mitigating Filter Bubbles Under a Competitive Diffusion Model - Banerjee, Prithu; Chen, Wei; Lakshmanan, Laks V.S. (Proceedings of the ACM SIGMOD International Conference on Management of Data (SIGMOD), 2023)
While social networks greatly facilitate information dissemination, they are well known to have contributed to the phenomena of filter bubbles and echo chambers. This in turn can lead to societal polarization and erosion of trust in public institutions. Mitigating filter bubbles is an urgent open problem. Recently, approaches based on the influence maximization paradigm have been proposed in our community for mitigating filter bubbles by balancing exposure to opposing viewpoints. However, existing works ignore the inherent competition between the adoption of opposing viewpoints by users. In this paper, we propose a realistic model for the filter bubble problem, which unlike previous work, captures the competition between opposing opinions propagating in a network as well as the complementary nature of the reward for exposing users to both those opinions. We formulate an optimization problem for mitigating filter bubbles under our model. We establish several evidences of the intrinsic difficulty in developing constant approximation to the problem and develop a heuristic and two instance-dependent approximation algorithms. Our experiments over 4 real datasets show that our heuristic far outperforms two state-of-the-art baselines as well as other algorithms in both efficiency and mitigating filter bubbles. We also empirically demonstrate that our best heuristic performs close to the optimal objective, which is obtained by utilizing the theoretical bounds of our approximation algorithms.